Cloprostenol, a synthetic analog of prostaglandin F2α induces functional regression in cultured luteal cells of felids. Issue 1 (16th April 2021) - Hryciuk, Michał M; Jewgenow, Katarina; Braun, Beate C
Abstract: In the present study, we investigated the effect of the synthetic analog of prostaglandin F2α (PGF2α)—cloprostenol—on cultured steroidogenic luteal cells of selected felid species over a 2-day culture period. The changes induced by cloprostenol were measured based on progesterone concentration and mRNA expression analysis of selected genes. Cloprostenol significantly reduced concentration of progesterone in cell culture medium of small luteal cells isolated from domestic cat corpora lutea (CL) at the development/maintenance stage ( P < 0.05), but did not influence progesterone production in cultured cells from the regression stage. A decrease or complete silencing of progesterone production was also measured in cultured luteal cells of African lion (formation stage) and Javan leopard (development/maintenance stage). Gene-expression analysis by real-time PCR revealed that treatment with cloprostenol did not have an influence on expression of selected genes coding for enzymes of steroidogenesis ( StAR, HSD3B, CYP11A1 ) or prostaglandin synthesis ( PTGS2, PGES ), nor did it effect hormone receptors ( AR, ESR1, PGR, PTGER2 ), an anti-oxidative enzyme ( SOD1 ) or factors of cell apoptosis ( FAS, CASP3, TNFRSF1B, BCL2 ) over the studied period. Significant changes were measured only for expressions of luteinizing hormone ( P < 0.05), prolactin ( P < 0.05) and PGF2α receptors ( P < 0.005) ( LHCGR, PRLR, and PTGFR ). The obtained results confirm that PGF2α/cloprostenol is a luteolytic agent in CL of felids and its impact on progesterone production depends on the developmental stage of the CL. Cloprostenol short-term treatment on luteal cells was associated only with functional but not structural changes related to luteal regression. Abstract : In cultured luteal cells of felids, cloprostenol can cause functional regression by reducing progesterone secretion and down-regulating expression of luteinizing hormone receptor, prolactin receptor, and prostaglandin F2α receptor.